2012
DOI: 10.1136/bmjopen-2011-000764
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced involvement of general practitioners in cancer rehabilitation: a randomised controlled trial

Abstract: ObjectiveTo test the hypothesis that a multimodal intervention giving the general practitioner (GP) an enhanced role in cancer rehabilitation improves patients' health-related quality of life and psychological distress.DesignCluster randomised controlled trial. All general practices in Denmark were randomised to an intervention group or to a control group. Patients were subsequently allocated to intervention or control (usual procedures) based on the randomisation status of their GP.SettingAll clinical departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…As a result, this review finally includes seven RCTs reported in eight papers and three descriptive quantitative studies. One RCT was reported in two papers which assessed different types of outcomes [3132]. The results of the quality appraisal of the studies can be found in Tables 5 and 6 (included studies), and Appendix 7 (excluded study), and the examples of the appraisal process with the checklist can be found in Appendix 5, 6, and 7.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, this review finally includes seven RCTs reported in eight papers and three descriptive quantitative studies. One RCT was reported in two papers which assessed different types of outcomes [3132]. The results of the quality appraisal of the studies can be found in Tables 5 and 6 (included studies), and Appendix 7 (excluded study), and the examples of the appraisal process with the checklist can be found in Appendix 5, 6, and 7.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that the intervention had no statistically significant effect on the patients' quality of life as the primary outcome 22 or on the level of psychological distress, 22 on GPs' proactivity or on the patients' participation in rehabilitation activities 23 as secondary outcomes. In this light, one might question whether we could reasonably expect any effect on patient satisfaction.…”
Section: Introductionmentioning
confidence: 93%
“…Since we did not have any data to estimate the effect of clustering prior to the study, we attempted to include patients in each group from a minimum of 144 practice units, allowing for maximum clustering. 22 Allowing for maximum clustering concerning HRQOL turned out to be very conservative (95% intracluster correlation coefficient 0.000 to 0.103). 22 It is plausible that the cluster effect is similarly low concerning the outcomes of this study.…”
Section: Gp Datamentioning
confidence: 99%
See 1 more Smart Citation
“…An early study analyzed the interactions of proteins involved in human ataxias to gain understanding of their biological interdependencies and to map their links to known neurodegeneration proteins 82 . To my knowledge this was the first large-scale systematic experimental protein-protein interaction map of a human disease and showed that ataxia-related proteins interacted with each other to a much higher degree than one would expect by random.…”
Section: ) Protein-protein Interaction Network For Understanding Comentioning
confidence: 99%